Polyathia longifolia: Redox potential of a cellulose nanocrystal derivative and ADMET predictions of selected compounds. (March 2022) - Otuechere, Chiagoziem Anariochi; Adewuyi, Adewale; Salau, TiOluwani Bamidele; Neupane, Netra Prasad; Adebayo, Olusegun Lateef; Egunjobi, Motunrayo; Verma, Amita
Abstract: Cellulosic biomass, endowed with several hydroxyl groups, has been the source of nanomaterials and functionalized derivatives for biomedical applications. However, the effect of green-synthesized cellulose nanocrystals from Polyathia longifolia (PCN) on redox parameters in the rat cortex and cerebellum has not been evaluated. In the present study, eighteen male albino rats were randomly grouped as control, PCN-50 and PCN-100, and administered distilled water, 50, and 100 mg/kg body weight PCN once a day (per os ) for 14 consecutive days. Growth performance, biochemical, histological analyses were performed to monitor treatment-related parameters. PCN, at both doses, did not significantly ( p  > 0.05) alter the body weights, absolute organ weights, albumin, cortical and cerebellar catalase, and glutathione S-transferase levels. However, PCN significantly elevated aspartate aminotransferase, cortical and cerebellar glutathione, and lipid peroxidation levels. Interestingly, histological observations revealed normal-appearing neurons, hippocampus, and Purkinje layers. Furthermore, in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of nine ligands from Polyalthia longifolia established oral drug-like behavior. They showed 5-hydroxy-2 (5H)-furanone as the safest compound among all selected ligands. Our data provide insight into the redox potential of green synthesized cellulose nanocrystals in rat sub-brain sections. Highlights: Cellulose nanocrystal from Polyathia longifolia (PCN) was synthesized by green method. In vivo assays revealed no effects on albumin, cortical and cerebellar catalase, and glutathione S-transferase levels. PCN significantly elevated aspartate aminotransferase and cortical and cerebellar reduced glutathione. Histology did not show any adverse effects on neurons, hippocampus, and Purkinje layers. 5-hydroxy-2 (5H)-furanone, a bioactive ingredient of P. longifolia showed good promise of frug-likeness.